MUP Training / Mohd Zahlan Mustaffa ... [et al.] - Mustaffa, Mohd Zahlan; Abdul Malik, Muhd Reduan; Shamsuddin, Rasman Farish; Wan Muhammad, Wan Adafi; Jamaluddin, Fadhlil Azim (2001)
MUP's Training is a centre for student to enhance their talent and motivations. This company main business is offering motivation courses for students. They are stated in Alor Setar , Kedah. They started their first operation in January 2003